Exploring research trends in developmental psychology: a bibliometric study with VOSviewer - Mayang Sety, Febyarna Pasca; Azam, Naqi Dahamat; Arshat, Zarinah; Ma’rof, Aini Azeqa (Human Resource Management Academic Research Society, 2024)
The field of developmental psychology has undergone significant evolution over the years, reflecting diverse theoretical frameworks, methodological approaches, and research interests. As this discipline continues to grow, it becomes important to understand the trends and shifts that characterize its development. The purpose of this study is to explore research trends in developmental psychology over the past two decades using literature review through bibliometric analysis. This study utilizes 200 articles related to developmental psychology, published between 2004 and 2024, from international journals indexed in Scopus. The research trends in developmental psychology are visualized using the VOSviewer software version 1.6.20. The results indicate that research trends in developmental psychology have been declining over the past 20 years. It is recommended that future research in developmental psychology explore underrepresented topics, such as the relationship between friendship and grit or personality and trauma, to diversify and deepen the field’s understanding. Finally, by studying research trends in developmental psychology across different periods, this study identifies key research hotspots and their evolution within the field. We hope that these findings will contribute and support the continued advancement and growth of developmental psychology field.